Model Implementasi Telemedicine Berbasis Teknologi Informasi di Puskesmas Kotabumi Ilir - Yulina; Servita Qodoria; Fazar Pratama (LPPM Universitas Muhammadiyah Kotabumi, 2025)
The development of information technology is driving the transformation of health services through the use of telemedicine, particularly in community health centers (Puskesmas) as first-level health facilities that play a strategic role in improving access and quality of public health services. However, its implementation still faces technical, organizational, and environmental challenges, necessitating a study on the readiness and implementation model of telemedicine at the Sindang Sari Community Health Center in Kotabumi. The urgency of this research lies in the need to map the actual readiness of community health centers in adopting telemedicine sustainably and formulate a contextual implementation model according to the characteristics of primary health care. The novelty of this research is demonstrated through the use of the Technology–Organization–Environment (TOE) Framework to analyze the implementation of telemedicine in an integrated manner using a case study approach. The problem formulation focuses on the level of readiness for telemedicine implementation, the technological, organizational, and environmental factors that influence it, and an effective implementation model. This study aims to analyze community health center readiness, identify determinants of implementation, and develop an applicable implementation model. The research method employed a qualitative approach through in-depth interviews, observation, and documentation, with thematic data analysis based on the TOE Framework. The results indicated that readiness was in the moderately prepared category, with the technology dimension dominating, while the organizational and environmental dimensions still needed strengthening. The conclusion confirms that successful telemedicine implementation requires the ongoing integration of technological readiness, organizational capacity, and environmental support.